2022
DOI: 10.5430/wjel.v12n8p260
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Video- and Audio-Assisted Reading on Saudi EFL Learners’ Reading Fluency and Comprehension

Abstract: To be successful, students must have excellent reading abilities, as reading is the most important skill for achieving high levels of learning and personal development. This study aims to investigate the effectiveness of using audio-visual aids to develop reading fluency and comprehension among English language students of the University of Jeddah. This quantitative research employed a quasi-experimental method. Data were collected from a reading comprehension test and a reading fluency test, measuring student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Tuan (2011) carried out an action research study and found that WebQuest enhanced students' reading skill. In Saudi Arabia context, Al Mahmud (2022b) was interested in investigating the impact of audiovisual aids to improve students' reading fluency. The findings show that audio-visual aids have positive effects on developing students reading skill in EFL.…”
Section: Use Of Technology For Teaching Language Skillsmentioning
confidence: 99%
“…Tuan (2011) carried out an action research study and found that WebQuest enhanced students' reading skill. In Saudi Arabia context, Al Mahmud (2022b) was interested in investigating the impact of audiovisual aids to improve students' reading fluency. The findings show that audio-visual aids have positive effects on developing students reading skill in EFL.…”
Section: Use Of Technology For Teaching Language Skillsmentioning
confidence: 99%
“…The Research by Semtin and Maniam (2015) concluded that application of skimming, scanning and questioning techniques can fix the EFL learners' problems in reading comprehension. Al Mahmud, (2022), in his study, also insisted on integrating new approach to traditional one for Saudi EFL learners' reading comprehension improvement.…”
Section: Difficulties and Problems In Reading Techniques For Learnersmentioning
confidence: 99%